Constraints to Productive Employment Faced by Safety Nets Beneficiaries in the Sahel : Results of a Multi-Country Qualitative Assessment - Bossuroy, Thomas; Koussoube, Estelle; Premand, Patrick (World Bank, Washington, DC, 2020)
In the Sahel subregion, which extends over Central and Western Africa, low labor productivity poses a challenge to poverty reduction, economic growth, and social stability. Social Safety Net Projects target the poorest households who derive their livelihoods from low-productivity activities. As such, they have the potential to improve labor productivity. As part of the Sahel adaptive social protection program (ASPP), the World Bank supports the design and implementation of productive accompanying measures for safety nets beneficiaries. This report sets out the results of a qualitative assessment of the constraints to productive employment that was conducted in the Social Safety Net Project areas, across five of the six countries covered by the ASPP: Burkina Faso, Mali, Niger, Senegal, and Chad. This assessment identified the main challenges to productivity growth in farm and nonfarm sectors and, jointly with other surveys and local and regional consultations, helped define accompanying measures to safety nets programs aimed at increasing current employment productivity and generating more productive jobs.